The Impact of Generation Z’S Perception, Buying Interest, and Social Media Towards Purchase Decision in Cinema XXI Ticket Sales Over the Years - Cecilia Endra; Felicia Angelina Tantono; Jerica Alverina; Putri Nadia Vanessa; Veriessa (MultiTech Publisher, 2020)
The abstract of